IMPLIKASI PUTUSAN NOMOR 34/PUU-XI/2013 MENGENAI JUDICIAL REVIEW PASAL 268 AYAT (3) TERHADAP UPAYA HUKUM LUAR BIASA PADA KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Inten Sri Damayanti, I Dewa Ayu; Putrawan, Suatra (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
The extraordinary remedy appeals in the form of invocation the judicial review arearranged in terms of the Book of Criminal Procedure Law (Kitab Undang-UndangHukum Acara Pidana-KUHAP) now can submitted more than once, according to thedecision issued by the Constitutional Court in the decision number 34/PUU-XI/2013.Itseems unfair if article 268 subsection (3) continues to apply, because the filingrestrictions of judicial review for the second time by the convicted or his heirs woundedsense of justice before the law (Article 28 D subsection (1) of the Republic of IndonesiaConstitusional 1945). Through normative legal research, this article aims to explain theimplication of the judicial decision number 34/PUU-XI/2013 against the provision ofarticle 268 subsection (3) KUHAP.
Keywords: The extraordinary remedy, Review Appeals, Criminal Procedure Law, The convictedor his Heirs